Astrocytes: new players in progressive myoclonus epilepsy of Lafora type. (1st February 2018) - Rubio-Villena, Carla; Viana, Rosa; Bonet, Jose; Garcia-Gimeno, Maria Adelaida; Casado, Marta; Heredia, Miguel; Sanz, Pascual
Abstract: Lafora disease (LD) is a fatal form of progressive myoclonus epilepsy characterized by the accumulation of insoluble poorly branched glycogen-like inclusions named Lafora bodies (LBs) in the brain and peripheral tissues. In the brain, since its first discovery in 1911, it was assumed that these glycogen inclusions were only present in affected neurons. Mouse models of LD have been obtained recently, and we and others have been able to report the accumulation of glycogen inclusions in the brain of LD animals, what recapitulates the hallmark of the disease. In this work we present evidence indicating that, although in mouse models of LD glycogen inclusions co-localize with neurons, as originally established, most of them co-localize with astrocytic markers such as glial fibrillary acidic protein (GFAP) and glutamine synthase. In addition, we have observed that primary cultures of astrocytes from LD mouse models accumulate higher levels of glycogen than controls. These results suggest that astrocytes may play a crucial role in the pathophysiology of Lafora disease, as the accumulation of glycogen inclusions in these cells may affect their regular functionality leading them to a possible neuronal dysfunction.